Attitude changes, modelling travel behaviour, and ex ante project evaluations - Bert van Wee; Maarten Kroesen (Transportation Research Interdisciplinary Perspectives, 2022)
The literature has increasingly recognized that people’s attitudes can change for many reasons. This paper argues that attitude changes can have important implications for modelling travel behaviour and ex ante evaluations of candidate policy options. Limiting ourselves to the transport system and the built environment, we discuss why attitudes could change, how these changes are not addressed in current aggregate travel behaviour models, mainly the four step model, and how they could influence the assessment of candidate policy options. We suggest related avenues for future research. The core point we want to make is that attitude changes are not included in aggregate models, which leads to an underestimation of the impacts (often: benefits) of unconventional transport policy options.